Intrahousehold distribution and child poverty: Theory and evidence from Côte d'Ivoire - Olivier Bargain; Olivier Donni; Prudence Kwenda (Institute for the Study of Labor (IZA), 2011)
Poverty measures in developing countries often ignore the distribution of resources within families and the gains from joint consumption. In this paper, we extend the collective model of household consumption to recover mother's, father's and children's shares together with economies of scale, using the observation of adult-specific goods and an extended version of the Rothbarth method. The application on data from Côte d'Ivoire shows that children command a reasonable fraction of household resources, though not enough to avoid a very large extent of child poverty compared to what is found in traditional measures based on per capita expenditure. We find no significant evidence of discrimination against girls, and educated mothers have more command over household resources. Baseline results on children's shares are robust to using alternative identifying assumptions, which consolidates a general approach grounded on a flexible version of the Rothbarth method. Individual measures of poverty show that parents are highly compensated by the scale economies due to joint consumption.
urn:nbn:de:101:1-201110263723
Keywords: D11; D12; D36; I31; J12; 330; collective model; consumer demand; Engel curves; Rothbarth method; cost of children; bargaining power; sharing rule; scale economies; equivalence scales; indifference scales; Kinder; Armut; Privater Haushalt; Verbraucherausgaben; Mikroökonomische Konsumfunktion; Haushaltsökonomik; Elfenbeinküste